2015
DOI: 10.1001/jamapsychiatry.2014.3053
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone vs Placebo for the Treatment of Alcohol Dependence

Abstract: IMPORTANCE Alcohol use disorder is one of the leading causes of disability worldwide. While effective pharmacological treatments exist, they are efficacious only in certain individuals, contributing to their limited use. Secondary analysis of clinical trial data suggests that a functional polymorphism (rs1799971, Asn40Asp) of the μ-opioid receptor gene (OPRM1) is associated with the risk of relapse to heavy drinking following treatment with the opioid antagonist naltrexone. OBJECTIVE To prospectively examine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 42 publications
(19 reference statements)
1
76
2
2
Order By: Relevance
“…Prescription of naltrexone, instead of acamprosate, for all AUD carriers of a G-allele could improve the overall treatment effectiveness, by preventing more relapses and therefore reducing costs associated with AUD. However, a recent study did not support previous findings on OPRM1 genotype-guided treatment allocation in AUD patients [22].…”
Section: Introductioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Prescription of naltrexone, instead of acamprosate, for all AUD carriers of a G-allele could improve the overall treatment effectiveness, by preventing more relapses and therefore reducing costs associated with AUD. However, a recent study did not support previous findings on OPRM1 genotype-guided treatment allocation in AUD patients [22].…”
Section: Introductioncontrasting
confidence: 57%
“…In our base-case analysis, assuming an effect of the OPRM1 genotype, we showed that OPRM1 screening can be cost-effective. However, these results need to be interpreted very carefully as recent evidence did not confirm prior data on OPRM1 pharmacogenetics in AUD [22]. On average, the genotype strategy is slightly more expensive, but also slightly more effective compared to no genotyping strategy.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the German PREDICT study (total N=426), modeled after the COMBINE study, there was no difference among naltrexone, acamprosate, and placebo groups on the time to first heavy drinking (Mann et al 2013). In a 12-week, low-risk-of-bias trial, subjects (N=221) were randomly assigned to 50 mg/day oral naltrexone or placebo in blocks on the basis of their OPRM1 genotype (Oslin et al 2015). There was no difference in the odds of heavy drinking with naltrexone as compared with placebo for either genotype, although significant reductions in heavy drinking occurred in all treatment groups.…”
Section: Benefits Of Naltrexonementioning
confidence: 99%
“…Since the AHRQ review, additional studies have not found a relationship between genotype and naltrexone response. As described above, one study randomly assigned subjects (N=221) to 50 mg/day oral naltrexone or to placebo with stratification on the basis of their OPRM1 genotype (Oslin et al 2015). In this 12-week trial, there was no difference in the odds of heavy drinking with naltrexone as compared with placebo for either genotype.…”
Section: Benefits Of Naltrexonementioning
confidence: 99%